ASSOCIATION BETWEEN CENTRAL RETINAL THICKNESS AND VISUAL OUTCOME POST INTRAVITREAL RANIBIZUMAB INJECTION LOADING DOSES IN EXUDATIVE AGE RELATED MACULAR DEGENERATION - Ramadhan, Ferdian; Yustiarini, Ima; Prakosa, Ady Dwi; Widjaja, Sauli Ari; Sasono, Wimbo; Firmansjah, Muhammad (International Journal of Retina, 2021)
Introduction : Age Related Macular Degeneration (AMD) stills the leading cause of blindness in developing countries for age 50 and above, increasing along higher life expectations.Anti- VEGF is the mainstay management for exudative AMD and able to reduce the central retinal thickness (CRT) and to increase the visual outcome. The aim of this study is to correlate between CRT and visual outcome in exudative AMD post intravitreal ranibizumab injection loading doses in Soetomo general academic hospital, Surabaya Methods : This was a retrospective, cross sectional study. Fourty two eyes who met inclusion criterias were received monthly loading doses of 0.5 mg Ranibizumab intravitreal injection for three consequtives months. Baseline visual acuity (BCVA) was measured with Snellen Chart converted to LogMAR, CRT was measured by SD-OCT. Parameters was measured before the first injection and after completed three months injections. Result : Fourty two eyes were composed by 59.5% male and 40.5% female with higher incidence in 61-70 years old (47.6%). Mean BCVA were 0.831 before and 0.624 after injection of serial Ranibizumab. Mean CRT were 346.9 and 254.2 µm before and after injection respectively. There was significant comparison between CRT and BCVA (p=0.00) & no correlation between CRT and BCVA before and after injection of Ranibizumab loading doses (p=0.418 & p=0.275) Conclusion : There were no correlation statistically between CRT and BCVA before and after injection of loading doses Ranibizumab intravitreal in exudative AMD. Further studies may be needed to prove the etiology of this tendencies.